In vitro Interaction of Metformin with Diclofenac in Aqueous Medium - Saha, Shuvashis; Begum, Rehana; Sultan, Md Zakir; Amjad, Farhad Md; Amran, Md Shah; Hossain, Md Amjad (Dhaka University Journal of Pharmaceutical Sciences, 2013)
Combination therapy may be unavoidable and common way for the treatment of disease where two or more drugs are given concurrently. The drugs may exhibit effects independently or may interfere with each other. Metformin is an anti-diabetic drug and diclofenac is a NSAID. The in vitro interaction of metformin with diclofenac was studied at room temperature and at different pH conditions. The studies were performed by various UV-Visible spectrophotometric, conductometric and HPLC methods. It was found that metformin formed stable 1:1 complex with diclofenac. The interaction may greatly influence the activity of these molecules. DOI: http://dx.doi.org/10.3329/dujps.v11i2.14555 Dhaka Univ. J. Pharm. Sci. 11(2): 101-106, 2012 (December)